Gioconda Belli. El Ojo de la Mujer (1974) And God created woman: outwardly and inwardly - González Montes, Antonio (2021)
In this paper we approach some poems of Gioconda Belli’s book, El Ojo de la Mujer (1991), where she recognizes that the creation of woman was the responsibility of God and that God built her outwardly and inwardly so that she, in turn, could serve the function of being “a workshop of human beings”. For this reason, she vindicates her condition as a woman and, in many poems, reiterates the vital role she played in the work of creation. Gioconda Belli gives special value to this mission, as part of the vindication of women of today, using an agile, fluid, metaphorical, transparent, clear and poetry appealing to both men and women.